Efficient biobanking of human lung tissue slices enabled by advanced ice-free cryopreservation - Saskia Altmaier; Frank Ihmig; Klaudia Grieger; Vanessa Neuhaus; Helena Obernolte; Florian Schmieder; Stephan Behrens; Ina Meiser; Julia Neubauer; Frank Sonntag; Katherina Sewald; Heiko Zimmermann (Cryobiology, 2025)

Cryopreservation of IPSCs-derived 3D organoids: A biomedicine key technology enhanced by Raman-microspectroscopy - Saskia Altmaier; Frank Stracke; Ina Meiser; Julia C. Neubauer; Heiko Zimmermann (Cryobiology, 2025)

Cytoskeleton adaptation to stretchable surface relaxation improves adherent cryopreservation of human mesenchymal stem cells - Saskia Altmaier; Ronan Le Harzic; Frank Stracke; Anna Martina Speicher; Detlev Uhl; Johannes Ehrlich; Thomas Gerlach; Katharina Schmidt; Katja Lemmer; Franziska Lautenschläger; Holger Böse; Julia C. Neubauer; et al. (Cryobiology, 2024)

Enhanced cryopreservation efficiency of HIPSC-Derived neural organoids based on raman studies - Saskia Altmaier; Ina Meiser; Frank Stracke; Ronan Le Harzic; Julia C. Neubauer; Heiko Zimmermann (Cryobiology, 2023)

A novel human pluripotent stem cell-based assay to predict developmental toxicity - Karin Lauschke; Anna Kjerstine Rosenmai; Ina Meiser; Julia Christiane Neubauer; Katharina Schmidt; Mikkel Aabech Rasmussen; Bjørn Holst; Camilla Taxvig; Jenny Katarina Emnéus; Anne Marie Vinggaard (Archives of Toxicology, 2020)
There is a great need for novel in vitro methods to predict human developmental toxicity to comply with the 3R principles and to improve human safety. Human-induced pluripotent stem cells (hiPSC) are ideal for the development of such methods, because they are easy to retrieve by conversion of adult somatic cells and can differentiate into most cell types of the body. Advanced three-dimensional (3D) cultures of these cells, so-called embryoid bodies (EBs), moreover mimic the early developing embryo. We took advantage of this to develop a novel human toxicity assay to predict chemically induced developmental toxicity, which we termed the PluriBeat assay. We employed three different hiPSC lines from male and female donors and a robust microtiter plate-based method to produce EBs. We differentiated the cells into cardiomyocytes and introduced a scoring system for a quantitative readout of the assay—cardiomyocyte contractions in the EBs observed on day 7. Finally, we tested the three compounds thalidomide (2.3–36 µM), valproic acid (25–300 µM), and epoxiconazole (1.3–20 µM) on beating and size of the EBs. We were able to detect the human-specific teratogenicity of thalidomide and found the rodent toxicant epoxiconazole as more potent than thalidomide in our assay. We conclude that the PluriBeat assay is a novel method for predicting chemicals’ adverse effects on embryonic development.

Automatisierte Kultivierung von induziert pluripotenten Stammzellen - Ina Meiser; Isabelle Sébastien; Julia C. Neubauer (BIOspektrum, 2013)